Data governance in the renewable energy development: issues and challenges - Zulhuda, Sonny (State Polytechnic of Sriwijaya, Indonesia, 2016)
Central to the development of the renewable energy is the optimization of the resources and power despite its intermittent characteristics. To this end, the information and storage system needs to be properly managed and governed. Therefore, ICT and its deployment in the renewable sector becomes a governance issue, not a mere matter of business process or technicalities. This paper looks at the criticality of information system in relation to the renewable energy sector. It also identifies relevant data risks primarily the data security and privacy risks, and then examines the scope required for data governance. This is a work in progress to introduce the issues and challenges in relation to data governance in the renewable energy development.